Western Song Singing Model to Improve Junior High School Studentsâ€™ Singing Ability in Indonesia (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
Singing activities are general activities that seem very easy. It could be said that anyone can sing. However, to be able to sing well and correctly seems to need to be learned. For Junior High Schools in Indonesia, singing activities are included in the teaching material of cultural arts sub music material. This study aims to â€œanalyze how singing activities are taught in classes on learning Art and sub music materialâ€. The approach of this research is interdisciplinary which involves music disciplines and music learning. The research method applied is interpretive qualitative. The research location is Semarang, by involving Semarang Junior High School Students and Teachers as the subject of research. Data collection techniques used in this research is observation, interviews, and documentation studies. The data validity technique is using data source triangulation. Data analysis techniques used in this research are interactive flow. The results showed that teachers taught singing, both in classes Vll, Vlll, and Vlll. Singing activity for class Vll focused on basic singing techniques. The eighth grade is focused on singing, whose vocals or singing techniques are more applied to singing local songs and Nusantara songs. Meanwhile, singing activity in class VIII is more focused on improvising any song. This study concludes that teachers always emphasize the use of western song singing models as a basic technique, regardless of the type of song used in the learning process.